2018
DOI: 10.1016/j.celrep.2018.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Sex Differences of Noradrenergic Neurons in the Mouse Locus Coeruleus

Abstract: SUMMARY Preclinical work has long focused on male animals, though biological sex clearly influences risk for certain diseases, including many psychiatric disorders. Such disorders are often treated by drugs targeting the CNS norepinephrine system. Despite roles for noradrenergic neurons in behavior and neuropsychiatric disease models, their molecular characterization has lagged. We profiled mouse noradrenergic neurons in vivo, defining over 3,000 high-confidence transcripts expressed therein, including druggab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 39 publications
(51 reference statements)
3
91
0
Order By: Relevance
“…The emerging data on the genetic profile of LC neurons (Robertson et al, 2013;Chandler et al, 2014;Plummer et al, 2015Plummer et al, , 2017Mulvey et al, 2018;Chen et al, 2019) and the explosion in techniques for genetic neuroanatomy are likely to identify more genes that are differentially expressed across LC modules, such as axon guidance molecules, neurotransmitter receptors, and cotransmitter peptides. Ongoing studies of gene expression at the single-cell level must be extended throughout development, and combined with LC projection tracing, for a clear and complete picture of this complex system.…”
Section: Developmental and Genetic Characteristics Of Lc Neurons Defmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging data on the genetic profile of LC neurons (Robertson et al, 2013;Chandler et al, 2014;Plummer et al, 2015Plummer et al, , 2017Mulvey et al, 2018;Chen et al, 2019) and the explosion in techniques for genetic neuroanatomy are likely to identify more genes that are differentially expressed across LC modules, such as axon guidance molecules, neurotransmitter receptors, and cotransmitter peptides. Ongoing studies of gene expression at the single-cell level must be extended throughout development, and combined with LC projection tracing, for a clear and complete picture of this complex system.…”
Section: Developmental and Genetic Characteristics Of Lc Neurons Defmentioning
confidence: 99%
“…These methods reveal function-specific LC modules that differ in projection target and genotype. However, LC neurons produce a multitude of neurochemicals and express a variety of genes (Mulvey et al, 2018). A better understanding of this level of diversity in the LC will allow the development and targeted deployment of research tools and pharmacological probes that can assess the functional roles of distinct LC neuronal subpopulations.…”
Section: Charting a Path Forward By Developing A Multilevel Understanmentioning
confidence: 99%
“…In the second study, the authors used TRAP to examine sex differences in gene expression within the locus coeruleus (LC)—a region involved in several functions, including learning, anxiety, and arousal (Mulvey et al, ). While few differences were observed in LC serotonergic neurons, 152 genes were differentially expressed between male and female noradrenergic neurons.…”
Section: The Brain Heterogeneity Challengementioning
confidence: 99%
“…These structural differences, to some extent, can account for the different performances of some behaviors, such as arousal and stress-related psychiatric disorders between male and female subjects. Recently, a thorough transcriptional profiling survey with identification of more than 3,000 genes in LC have revealed substantial sex differences (>100 genes) of LC-NE neurons on a transcript level and further demonstrated that these differential gene expressions are able to generate sex-related different behavioral responses (Mulvey et al, 2018). However, to the best of our knowledge, no systematic and comprehensive analysis of brain-wide inputs to LC-NE neurons in male and female mice has been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the key role in regulating mammal neural networks, multiple studies have focused on LC and employed LC-NE neurons as paradigms for elucidating the underlying mechanisms of sex differences with regard to the effects of sex hormones, structural differences, and molecular mechanisms ( Pinos et al, 2001 ; Garcia-Falgueras et al, 2005 ; Bangasser et al, 2011 , 2016 ; De Carvalho et al, 2016 ; Mulvey et al, 2018 ). Among them, sex hormones have been shown to have a differential influence on the activities of LC-NE neurons in rats of different sexes ( De Carvalho et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%